Open Schooling: Addressing the Challenge of Out-of-School Youth - Commonwealth of Learning (2017)
Goal 4 of the Sustainable Development Goals aims to ensure inclusive and quality education for all and promote lifelong learning. One target is to ensure that all girls and boys complete free, equitable and quality primary and secondary education by 2030. Yet, this is impossible to achieve within present mainstream education systems. A new way of thinking about schooling is required. // Open Schooling is a model to address this problem without having a disruptive effect on mainstream schooling – a symbiotic relationship, where both systems can benefit from another, is possible. // A multidimensional approach is required. Part of the solution is to improve teaching and learning in conventional schools in order to decrease dropout and increase throughput, while also providing access to quality learning opportunities to out-of-school youth through innovative open schooling. Open schooling
Accepted: 2017-03-28T21:32:23Z Publisher: Commonwealth of Learning (COL) KerkoCite.ItemAlsoKnownAs: 2339240:H7D8S5HN 2405685:NKWVVEW4

Reaching the Unreached through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan: Final Report - Commonwealth of Learning (Commonwealth of Learning, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:L7RZVSRD 2405685:PXY96GW4